Early Fluid Accumulation and Intensive Care Unit Mortality in Children Receiving Extracorporeal Membrane Oxygenation. Issue 1 (January 2021) - Anton-Martin, Pilar; Quigley, Raymond; Dhar, Archana; Bhaskar, Priya; Modem, Vinai
Abstract : Purpose of this study was to evaluate the impact of early fluid accumulation and renal dysfunction on mortality in children receiving extracorporeal membrane oxygenation (ECMO). Retrospective cohort study of neonatal and pediatric patients who received ECMO between January 2010 and December 2012 in a tertiary level multidisciplinary pediatric intensive care unit (ICU). Ninety-six patients were included, and forty-six (48%) of them received continuous renal replacement therapy (CRRT) during ECMO. Overall mortality was 38.5%. Proportion of patients with acute kidney injury (AKI) at ICU admission was 33% and increased to 47% at ECMO initiation. High-risk diagnoses, extracorporeal cardiopulmonary resuscitation (ECPR), and venoarterial (VA)-ECMO were more common among nonsurvivors. Nonsurvivors had significantly higher proportion of AKI at ICU admission (OR: 2.59, p = 0.04) and fluid accumulation on ECMO day 1 (9% vs. 1%, p = 0.05) compared with survivors. Multivariable logistic regression analysis (adjusted for a propensity score based on nonrenal factors associated with increased mortality) demonstrated that fluid accumulation on ECMO day 1 is significantly associated with increased ICU mortality (OR: 1.07, p = 0.04). Fluid accumulation within the first 24 hours after ECMO cannulation is significantly associated with increased ICU mortality in neonatal and pediatric patients. Prospective studies evaluating the impact of conservative fluid management and CRRT during the initial phase of ECMO may help further define this relationship. Abstract : Supplemental Digital Content is available in the text.